The development of the public service commission system and the problems of recruitment into the public service in a plural society - Katagum, Sule. (Lagos : Federal Public Service Commission, 1974)
The Civil Service in Nigeria owes its origin to its British counterpart. In the United Kingdom, the foundations of the Civil Service were laid by the Northcote and Trevelyan Report in 1854. These two reports led to the emergence of the Civil Service Commission in the United Kingdom whose role was restricted mainly to the conduct of examinations for entry into the top classes of the Civil Service. By 1948, with the introduction of the Macpherson Constitution, nationalism had become more vocal and one its elements was a cry for more Nigerianisation of the Civil Service.
Text of a lecture at the Mid-West Public Service Forum on Friday, February 22, 1974.
nmn 19/04/2019, ne 19/08/2021
Loans
Keywords: Civil service; Civil service - recruitment; Nigeria